Power Devices: State Of The Art And Future Prospects - Baharin, Mohd Syamsul Nasyrik Samsol (2020)
Power Devices: Do You Know The Existence? Power adapter; 50% smaller than standard 61W MacBook Charger, 2.5 faster than a standard 1A Output, can power up all your USB-C Devices, From Smartphone To Laptops!. High speed trains. Electic Vehicle; DC/DC Converters, Inverters.